2010
DOI: 10.1021/jp106648c
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Oxygen Vacancy Density on the TiO2 Surface by La-Doping for Dye-Sensitized Solar Cells

Abstract: Facilitated by TiO2 particles absorbing La3+ in hydrosol, La-doped TiO2 was prepared by a sol-hydrothermal method. Electron paramagnetic resonance and Brunauer−Emmett−Teller (BET) surface area analysis showed that the obtained La-doped anatase TiO2 surface provided a higher density of oxygen vacancies without a change in the BET surface area. A theoretical calculation was carried out to explain the generation mechanism of the increased oxygen vacancies. The results showed that the La-doped anatase TiO2 (101) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
100
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(104 citation statements)
references
References 34 publications
3
100
1
Order By: Relevance
“…The overall conversion efficiency of solar light to electric power achieved was 5.97 % ( Table 2). Contrary to the observed behavior with anatase TiO 2 , [23] La doping was detrimental to brookite cell performances, even after the TiCl 4 treatment.…”
Section: Resultscontrasting
confidence: 90%
See 2 more Smart Citations
“…The overall conversion efficiency of solar light to electric power achieved was 5.97 % ( Table 2). Contrary to the observed behavior with anatase TiO 2 , [23] La doping was detrimental to brookite cell performances, even after the TiCl 4 treatment.…”
Section: Resultscontrasting
confidence: 90%
“…The observed behavior is opposite to that described recently by Zhang et al for the anatase phase. [23] The brookite cell performances were evaluated by recording J-V curves under normalized illumination of the cells (Figures 4 a and 4 b and Table 2). In the first step, DSSCs were prepared with TiO 2 layers not treated with the TiCl 4 solution after sintering and prior to sensitization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] The La 3d3/2 and La 3d5/2 peaks at binding energies of 837.6 and 854.2 eV, respectively, agree with the data reported previously for Ti-O-La bonds (Figure 3, c). [27] In summary, the XPS spectra illustrate that the La in the samples exists in the form of Ti-O-La.…”
Section: Resultsmentioning
confidence: 88%
“…The stoichiometry was further found to be a function of process parameters. Zhang et al [15] reported that oxygen vacancies at the surface remarkably prolonged the life of the photon-generated carrier. Thus, it significantly increased the activity.…”
Section: Introductionmentioning
confidence: 99%